Rationality, Relativism, and Religion: A Reinterpretation of Peter Winch - Schilbrack, Kevin (Sophia, 2009)
Many point to Peter Winch’s discussion of rationality, relativism, and religion as a paradigmatic example of cultural relativism. In this paper, I argue that Winch’s relationship to relativism is widely misinterpreted in that, despite his pluralistic understanding of rationality, Winch does allow for universal features of culture in virtue of which cross-cultural understanding and even critique is possible. Nevertheless, I also argue that given the kind of cultural universals that Winch produces, he fails to avoid relativism. This is because in order to provide the standards without which relativism ensues, one requires a certain kind of criteria of rationality, namely, what I here call substantive universals, a kind of criteria which Winch rejects.